An open-source tool for the validation of finite element models using three-dimensional full-field measurements. (March 2020) - Abel, Alexander; Kahmann, Stephanie L.; Mellon, Stephen; Staat, Manfred; Jung, Alexander
Highlights: Open-source tool for finite element model validation using full-field-measurements. Accurate point-set registration of real world data with no initialization required. Validation of a cemented hip arthroplasty model under compressive load. Abstract: Three-dimensional (3D) full-field measurements provide a comprehensive and accurate validation of finite element (FE) models. For the validation, the result of the model and measurements are compared based on two respective point-sets and this requires the point-sets to be registered in one coordinate system. Point-set registration is a non-convex optimization problem that has widely been solved by the ordinary iterative closest point algorithm. However, this approach necessitates a good initialization without which it easily returns a local optimum, i.e. an erroneous registration. The globally optimal iterative closest point (Go-ICP) algorithm has overcome this drawback and forms the basis for the presented open-source tool that can be used for the validation of FE models using 3D full-field measurements. The capability of the tool is demonstrated using an application example from the field of biomechanics. Methodological problems that arise in real-world data and the respective implemented solution approaches are discussed.